Persuasive Strategies in Jacinda Ardern's Speeches: A Critical Discourse Analysis of Women Leadership in Crisis - Sartika, Delita; Ulfiati, Lilik; Hidayati, Hidayati (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Traditional views of leadership often associate strong leadership with directness, decisiveness, and dominance, which are stereotypically coded as masculine while perceiving empathy and collaborative orientation–qualities commonly associated with femininity–as less compatible with effective leadership. However, contemporary research demonstrates the increasing importance of empathy in effective leadership, particularly during crisis situations. This study explores the persuasive strategies employed by New Zealand’s former Prime Minister Jacinda Ardern in her speeches following the 2019 Christchurch mosque shootings. Using a qualitative descriptive approach, this study applies discourse analysis to six transcripts of speeches by Jacinda Ardern to identify discourse patterns that demonstrate her persuasive strategies and examined how these patterns function in crisis communication. The findings revealed three critical elements of Ardern’s persuasive strategies: combining transparency and compassion to foster trust, demonstrating clarity and decisiveness to establish authority, and using motivational and forward-looking discourse to inspire collective action. These elements demonstrate how Ardern’s empathetic communication helped build trust and encourage compliance, while her directive and decisive language facilitated actionable resolution, which enabled the nation’s swift recovery. By critically challenging persistent gender stereotypes in leadership that frame empathy and decisiveness as mutually exclusive traits, this study underscores the transformative potential of empathetic leadership in managing crise and advances gender equity in leadership discourse.